(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2025)
The results showed that compared to irrigated circumstances, crop height, effective panicles per m², and grain production were all 22% lower under moisture-restricted conditions. Among the strains tested, IR17L1387, IR16L1713, and IR16L1801 had the best stress tolerance index (STI), suggesting that they might thrive in environments with limited water availability. Sukhadhan 3 genotype showed the highest degree of stability in both settings, according to GGE biplot analyses (Which-Won-Where and Mean vs. Stability). Furthermore, under conditions where moisture was scarce, the winning genotype was IR16L1713, while in conditions where water was abundant, the winning genotype was IR17L1387.